Profitability as a Mediating Factor in the Effect of Capital Structure on Stock Prices: An Empirical Study of Companies Listed in the MNC36 Index on the Indonesia Stock Exchange. - Widyawati, Silvia; Akhmadi, Akhmadi; Khaerunnisa, Enis (Journal of Economics, Management, Accounting and Computer Applications, 2025)
This study examines the role of profitability in influencing capital structure on stock prices in companies listed on the MNC36 Index. The population in this study were MNC36 Index companies for the 2018-2023 period. The sample used in this study was 9 companies, determined using a purposive sampling technique, resulting in a total of 54 observational data. The analysis techniques used in this study were descriptive statistics, classical assumption tests, multiple regression, and hypothesis testing using SPSS 23 analysis tools. The results show that capital structure significantly affects stock prices and profitability, but profitability does not mediate the relationship, and firm size does not significantly control stock price variations. These findings suggest that debt management remains important to investor perceptions. Future research should consider sectoral contexts and alternative variables.